Shaping college students' sports values from the perspective of Olympic Culture: Theoretical logic, practical significance, and path exploration - Ying, Guo; Jianshuo, Dun; WenTao, Lin (Journal of Islamic, Social, Economics and Development, 2025)
The Olympic spirit is an important part of human civilization, embodying ideals of peace, friendship, unity, fairness, respect, and excellence. It is also a cross-cultural value system that emphasizes the significance of sports and the values brought by sports, including health, friendship, unity, and fair competition. The core logic of the transformation of modern sports values lies in the modernization of sports culture. As a mindset and value orientation, sports values represent an individual’s recognition, emotional identification, and willingness to practice the value of sports. This article, from the perspective of cultural symbiosis theory, proposes the theoretical logic of constructing a stable core value orientation, deconstructing the traditional direction of the Olympic motto, and realizing the lasting penetration of the modernization of sports values. By studying the Olympic spirit demonstrated by athletes at the 2024 Paris Olympics, the practical significance and path exploration of the Olympic spirit in shaping college students' sports values are explored, with the aim of promoting the formation of correct sports values among college students.